Kelimpahan Mikroplastik pada Kerang Kepah (Polymesoda sp.) di Perairan Sungai Jada Bahrin, Bangka dan Kerang Tebelan (Lingula sp.) di Perairan Pantai Pekapor, Bangka Selatan - Angelia Nurtastbita Pratiwi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
The lack of information related to the content of microplastics accumulated in shellfish in the Bangka region, especially in the type of shellfish consumption Polymesoda sp. and Lingula sp. potentially pose a risk to food safety. Therefore, this study was conducted to analyze the type and abundance of microplastics in Polymesoda sp. shellfish. and Lingula sp. Data collection will be carried out in December 2022 – February 2023 in the waters of Jada Bahrin Village and in the waters of Pekapor Beach, Permis Village. The sampling method uses random purposive sampling with 3 countermeasures groups. Sample processing in the laboratory uses H2O2 as the destruction material and NaCl to increase density. The results showed that there were microplastic particles in both shellfish samples including fibers, fragments and films with fiber types dominating in both samples. Average total abundance of microplastics Polymesoda sp. amounted to 0.33 particles/individual, while the average total abundance of microplastics Lingula sp. by 0.65 particles/individual. The results prove that both shellfish samples have been contaminated with microplastics which threaten food safety and adversely affect human health, so deeper research is needed related to microplastic contamination such as chemical toxicants and substances, especially in consumption biota that affect food security and safety